Integrasi flipped classroom dan digital storytelling dalam pembelajaran deep learning untuk meningkatkan berpikir kritis dan kreativitas matematis peserta didik - Arifah, Raisya Zannuba; Arista, Sani Fauziyati; Susilawati, Wati; Sholihah, Wildatus (Papanda Journal of Mathematics and Science Research, 2025)
The title of this study reflects an idealistic vision of improving mathematics learning quality through innovative approaches; however, empirical evidence indicates that students’ problem-solving abilities, particularly in critical thinking and mathematical creativity, still require improvement. This study aims to examine the effectiveness of integrating deep learning, flipped classroom, and digital storytelling in enhancing students’ critical thinking and mathematical creativity. Using a quantitative experimental design with a pretest-posttest control group, the study involved 33 eight-grade students, devided into an experimental group and a control group. The findings showed a significant improvement in the experimental group compared to the control group, especially in the aspect of interpretation, evaluation, and inference. More students in the experimental group moved into higher performance categories after the intervention. These results indicate that the integration of flipped classroom and digital storytelling in deep learning-based mathematics instruction fosters students’ engagement, supports critical and creative thinking, and enhances their ability to apply mathematical concepts in real-world contexts.